RANCANG BANGUN QUESTION ANSWERING SYSTEM LAYANAN INFORMASI AKADEMIK BERBASIS RAG - Muhammad Surya Adhi Setiawan (CV. Adiba Aisha Amira, 2026)
The complexity of academic information in the New Student Admissions (PPMB) process often overwhelms conventional helpdesk services. This study aims to design and build a prototype Question Answering (QA) System based on Retrieval-Augmented Generation (RAG) that can automate information services accurately. The system is built using a three-layer architecture: Presentation Layer (Gradio UI), Application Layer (Python/LangChain), and Data Layer (ChromaDB). A key focus of the development is the data pipeline strategy, specifically handling